Indoor propagation channel measurement of ultra wideband antenna with robotic - Boonvisat, Satean; Promwong, Sathapom; Supanakoon, Pichaya; Kaewmechai, Sompoph; Sitiyopasakul, Pisan (My University, 2005)
In this paper, the characterization of ultra wideband (UWB) antenna with robotic is evaluated. The measurement system consists of transmitter (Tx) and receiver (Rx) biconical antennas measured by using a vector network analyzer (VNA). To obtaining the data, measurements were performed at 3 GHz to 11 GHz covered by a VNA, which provided information on the amplitude and phase of the transmission coefficient. Friis' transmission formula is not directly applicable and the waveform distortion may degrade the transmission performance as well. The matched filter is considered at the receiver side to maximize the SNR for evaluation. The power delay profile and the UWB transmission gain, based on the extension of Friis' transmission formula take into account the transmitted waveform and the matched filter into the system for the free space of UWB. The experimental examples using the biconical antenna as the receiver install with robotic are presented in this paper. © 2005 IEEE.
Keywords: Friis' transmission formula; Ultra wideband (UWB); Ultra Wideband Antenna with Robotic